Interactive Multimedia Based on a Contextual Approach to Improve the Science and Social Studies Learning Motivation of Fifth Grade Students - Ni Made Nova Andila Darmayanti; Nice Maylani Asril; Ni Wayan Rati (Jurnal Media dan Teknologi Pendidikan, 2026)
This research is motivated by the low learning motivation of fifth-grade students in science learning which is still dominated by conventional methods and less interesting media. The purpose of this study is to describe the effectiveness of interactive multimedia based on a valid, practical, and effective contextual approach to increase student learning motivation. The development model used is Research and Development (R&D) with the ADDIE approach (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were 17 fifth-grade students as media users. The data collection method and instrument used a questionnaire. The data analysis techniques used descriptive qualitative, quantitative, and inferential. The results of the study indicate that the developed multimedia is very valid in terms of material and design, practical to use in learning, and effective in increasing student learning motivation through interactive activities and contextual presentation. This research provides important implications for the development of technology-based learning media, especially in strengthening science learning that is more interesting, meaningful, and relevant to students' daily lives.